Engaging faculty in group-level change for institutional transformation : disrupting inequity and building inclusive academic departments /: disrupting inequity and building inclusive academic departments. (2023) - Jackson, J. Kasi; Anderson, Amena O; Dilks, Lisa M; Holmes, Maja Husar; Kunkle, Christine E; Nolan, James J; Latimer, Melissa
No abstract available